Pengendalian Kualitas Proses Produksi Paving Block K300 T-6 Dengan Menggunakan Metode Six Sigma Dan Failure Mode Effect Analysis (FMEA) Di PT. Pesona Arnos Beton - Qothrunnada, Alisa; Rochmoeljati, Rochmoeljati (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
PT Pesona Arnos Betom is manufacturing company engaged in the field of general contractor and supplier wich produces paving blocks, udith, box culverts, kanstin, sirtu, sand, coral, dark ash, and basecous. One of its superior products is the K300 T-6 paving block with a total production in February-August 2022 of 5,683,800 units and a total defect of 892,560 units. The purpose of this study is to control quality, minimize defects, and provide suggestions for improving the quality of the K300 T-6 paving block production process. This study uses the Six Sigma method and Failure Mode Effect Analysis (FMEA). From the results of the study, it can be seen that the average sigma value based on total defects from February to August 2022 is 3.43 sigma, which means that it still has not met the target towards the six sigma standard. The FMEA method is used to find out that gouge defects are dominant. Proposed improvements that need to be made are tightening the SOP for pallet arrangement and holding a pallet arrangement checking section, monitoring the loading and unloading process carried out by employees using heavy equipment, re-checking the dosage of hardener using automatic scales before being put into the mixer, checking the old ash content when producing dark ash before entering the paving production stage, and setting up the mixer machine for automatic 8 minutes operation.Keywords – FMEA, Paving Block, Quality Control, Six Sigma